Pengaruh Aplikasi Canva pada Materi Keanekaragaman Hayati terhadap Hasil Belajar Kognitif Siswa - Rizka Salsabila Nasution; Rohani Rohani (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
Canva is an interactive multimedia that provides educational functions that can be used as a tool to help skills, creativity and collaboration, thus making learning easier and more enjoyable. Canva's learning media can be used to assist the learning process, teachers can save time in designing learning media, and improve cognitive learning outcomes. The aim of the study was to determine the effect of the Canva application on biodiversity material on the cognitive learning outcomes of class X students of Batubara State Islamic Senior High School, Lima Puluh District, Batu Bara Regency. This type of research is a quasi experiment, with a non-equivalent control group design. The sampling technique used random sampling technique. The sample used was class X IPA-2 with 33 students as the experimental class, and class X-IPA 1 with 35 students as the control class. The research instrument was students' cognitive learning outcomes using a pre-test and post-test of 25 multiple choice questions regarding biodiversity material. The data analysis technique used is the normality test, homogeneity test, and hypothesis testing. The results showed that the cognitive learning outcomes of class X students at Batubara State Islamic Senior High School, Lima Puluh District, Batu Bara Regency in the subject of biodiversity taught using the Canva application experienced an increase in the average score from 45.70 to 84.85. Students' cognitive learning outcomes on biodiversity material taught without using the Canva application experienced an increase in the average score from 40.11 to 81.03. There is an effect of the Canva application on students' cognitive learning outcomes on biodiversity material in class X MA Negeri Batubara, Lima Puluh District, Batu Bara Regency which is proven through hypothesis testing with the acquisition of a significance value of 0.036 <0.05.